Santri’s Humility in the Salafiyyah Islamic Boarding School - Rahmatullah, Azam Syukur; Azhar, Muhammad; Fatwa, Ahmad Fajruddin (IAIN Samarinda, 2021)
This research belongs to qualitative research, which explored the tawadhu' (humility) in the Lirboyo Islamic Boarding School, Kediri. Tawadhu' in Islamic boarding school is traditional, rooted, and has become a positive character. Thus, it deserves to be explored and later can be used as a